(3GdchcH GdSGQj aj MbjbI GdLRA GdGNJjGQjs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd YHOGdZfj GdTgjQ HGHf GdfGHdSj GdTGej GdOeTbj gPg QSGdI aj HjGf ePGgH GdoeJcedejf aj CaYGd GdYHGO GdUGOQg efge Ydi hLg GdENJjGQ s
(3BNQgG (B:s
(3hEfeG GdCYeGd HGdfjGJ hEfeG dcd CeQA eG fhi hGddg CYde hCMce s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B394s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds